Impact of Appropriate Empirical Antibiotic Treatment on the Clinical Response of Septic Patients in Intensive Care Unit: A Single-Center Observational Study - Mateo Tićac; Tanja Grubić Kezele; Marina Bubonja Šonje (MDPI AG, 2024)
The appropriate antibiotic treatment of patients with bacterial sepsis in the intensive care unit (ICU) remains a challenge. Considering that current international guidelines recommend 7 days of antibiotic therapy as sufficient for most severe infections, our primary outcome was a comparison of clinical response to initial empirical therapy on day 7 and mortality between two groups of septic patients-with appropriate (AEAT) and inappropriate (IEAT) empirical antibiotic therapy according to the in vitro sensitivity of bacteria detected in a blood culture (BC). Adult patients admitted to the ICU between 2020 and 2023, who were diagnosed with sepsis according to the Sequential Organ Failure Assessment (SOFA) score ≥ 2 in association with a suspected or documented infection, were selected for the study. Of the 418 patients, 149 (35.6%) died within 7 days. Although the AEAT group had a lower mortality rate (30.3% vs. 34.2%) and better clinical improvement (52.8% vs. 47.4%) on day 7 after starting empirical antibiotic therapy, there was no significant difference. A causative organism was isolated from BCs in 30% of septic patients, with gram-negative bacteria (GNB) predominating in 60% of cases, and multidrug-resistant (MDR) or extensively drug-resistant (XDR) bacteria predominantly detected in the BCs of the IEAT group. Although the AEAT group had slightly worse clinical characteristics at the onset of sepsis than the IEAT group, the AEAT group showed faster improvement on days 7 and 14 of sepsis. In this retrospective cross-sectional study, the AEAT group was associated with better clinical response at day 7 after sepsis onset and lower mortality, but without a significant difference. Comorbidities and the type of bacterial pathogen should also be taken into account as they can also contribute to the prediction of the final outcome. These results demonstrate the importance of daily assessment of clinical factors to more accurately predict the clinical outcome of a septic patient.